Preparation and characterization of Ca1 -x La x Ti1 -x Co x O3 (0·00 - Parkash, O.M.; Durga Prasad, Ch.; Kumar, D. (Springer India, 1988)
The possibility of the formation of solid solution in the system Ca1 -x La x Ti1 -x Co x O3 for x≤0·5 has been investigated. X-ray diffraction studies show that compositions with x=0·05, 0·1, 0·2, 0·3 and 0·5 prepared by the ceramic method are single-phase materials. All the compositions have a structure similar to CaTiO3 with a pseudo-cubic unit cell. Preliminary studies show that interfacial polarization contributes significantly to their dielectric constant. © 1988 Indian Academy of Sciences.
Keywords: Calcium lanthanum titanium cobalt oxide; perovskite